Validity and Practicality of Smart Apps Creator Interactive Media in Pancasila Education for Elementary Schools - Saa’dah, Munnadiya; Reinita, Reinita; Wahyuni, Etri; Anita, Yesi (Journal of Educational Sciences, 2025)
This research is motivated by the fact that technology-based learning media is not yet optimally used by teachers in the learning process. Teachers have not yet provided students with the opportunity to use them directly and independently thru technological devices. This research aims to develop interactive media using Smart Apps Creator that is valid and practical. This research is a type of Research and Development study using the ADDIE model. Data was collected thru expert validation and teacher and student response practicality. The subjects of this research are fourth-grade students in one of the districts in Lima Puluh Kota Regency. The research results show that the interactive media developed using Smart Apps Creator is highly valid, with an average validity of 95.56%. The practicality test results of the interactive media show that it is very practical, with scores of 96% for teacher and 96.13% for student in the first school, 98% for teacher and 93.69% for student in the second school, and 96% for teacher and 95% for student in the third school. Thus, the interactive media developed using the Smart Apps Creator application is valid and practical for use in Pancasila Education learning in grade IV elementary school.